Dynamic regulation of PCNA ubiquitylation/deubiquitylation - Fox, Jennifer T. (2011)
Proliferating Cell Nuclear Antigen (PCNA) ubiquitylation plays a crucial role in maintaining genomic stability during DNA replication. DNA damage stalling the DNA replication fork induces PCNA ubiquitylation that activates DNA damage bypass to prevent the collapse of DNA replication forks that could potentially produce double strand breaks and chromosomal rearrangements. PCNA ubiquitylation dictates the mode of bypass depending on the level of ubiquitiylation; monoubiquitylation and polyubiquitylation activate error-prone translesion synthesis and error-free template switching, respectively. Due to the error-prone nature of DNA damage bypass, PCNA ubiquitylation needs to be tightly regulated. Here, we review the molecular mechanisms to remove ubiquitin from PCNA including the emerging role of USP1 and ELG1 in this fascinating process.